Influence Of Motivation To Work And Work Discipline Employee Performance Eating Chicken Geprek Sragen - ELA INTANI, MARLIAN, Soepatini, S.E., M.Si., Ph.D (2017)
This study aims to analyze the influence of motivation and discipline of work to employees performance geprek sragen eat chicken house. This type of research is quantitative research which is done at home employee geprek sragen eat chicken. The population in this study were all employees of the house to eat chicken geprek sragen many as 108 people with the determination of the sample is census method. The type of the source data used in this study are primary data. Research data collection techniques through a questionnaire with Likert scale. Data were analyzed using the validity test, reliability test, test classic assumptions (normality test, multicollinearity and test heterokedastisitas), as well as multiple linear regression (t-test, f, and test R2). Based on the survey results revealed that the variable Work Motivation and Work Discipline variable positive influence on employee performance variables of worker proven, indicated by the results of multiple linear regression analysis as follows: Y = 5.971 + 0.494 + 0,187X1 + e From this equation shows that the variable Work Motivation and variable Work Discipline positive effect on the variable employee performance while on t test results can be obtained variable work motivation with the value t = 3.949> table = 1.983, then Ho is rejected so that no significant effect Work Motivation to Performance employees. Work Discipline and variable calculation results obtained t = 7.565> table = 1.983, then Ho is rejected so that no significant effect on the Performance Work Discipline Employees. Likewise from the calculation of F test can be obtained by the value of F = 52.890> F table = 3.08, then Ho is rejected so that together there is significant influence work motivation (X1), Work Discipline (X2) the Employee Performance